If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 14 = 113 + -6 Reorder the terms: 14 + 5x = 113 + -6 Combine like terms: 113 + -6 = 107 14 + 5x = 107 Solving 14 + 5x = 107 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 5x = 107 + -14 Combine like terms: 14 + -14 = 0 0 + 5x = 107 + -14 5x = 107 + -14 Combine like terms: 107 + -14 = 93 5x = 93 Divide each side by '5'. x = 18.6 Simplifying x = 18.6
| 5x-(x-5)=-4+5x+8 | | 20+(-9)(-15)+-2= | | 1.005=0.95+0.005x | | 39x+33=462 | | (p-q)*(r-s-t)=0 | | 80-2x=56 | | 4x^(3/2)=16 | | 2(t-3)-3=7 | | (-4y+x-7)*x=0 | | x+4/3=x+6/5 | | 6[-3+7(-2+5)]= | | 3x+2xy+8=0 | | (2x+1)(2x-1)=3 | | (3x-2y+4)-(-6x+y-5)=0 | | (-2-2)[8+(7+8)]= | | (3x-2y+4)+(-6x+y-5)=0 | | 3x+5xy=8 | | y=7sin(x^2) | | x^2-50x+576=0 | | (5r+2s-t)-(-3r-s+6t)=0 | | (-15-2)(-20-7)= | | x+2x+(x+3)=7 | | 14-w=42 | | (11p-7q-r)+(3p+q-9r)+(-p-q+2r)=0 | | (-15-2)(-20)= | | 4x-2(x-3)=-8+5x-1 | | B*2A=bh | | 5+10=120 | | 13-(7-5*4)= | | (16x^2y^3z)/(-8x^3y^2z)=0 | | (6a^2b)*(14a^3b^2)=0 | | 9n-2-8n-15=-5 |